Status report of lipid-lowering trials in diabetes. - Betteridge, D; Colhoun, H; Armitage, J (2000)
The prevention and treatment of coronary heart disease is a major challenge in the overall management of the patient with type 2 diabetes. Diabetic dyslipidaemia is an important risk factor and is open to therapeutic intervention. However, as yet there are no primary or secondary coronary heart disease prevention trials of lipid-lowering therapy reported in diabetic populations. In this review, on-going clinical trials of lipid-lowering therapy in specific diabetic populations will be described.